Розвиток самозайнятості населення як шлях вирішення проблеми зайнятості - Андріанова, В.В. (Культура народов Причерноморья, 2013)
У статті висвітлені проблеми і перспективи розвитку самозайнятості населення в Україні.
Розглянуті і узагальнені сучасні теоретичні підходи до самозайнятості населення. Уточнено поняття
самозайнятого населення в сучасних економічних умовах. Визначені основні причини виникнення
самозайнятості і переходу населення України до роботи в умовах самостійної зайнятості, виявлені
резерви зростання чисельності самозайнятого населення. Розкриті особливості самозайнятості в
умовах інформаційного суспільства. Обгрунтована необхідність державної підтримки розвитку
самозайнятості населення шляхом вдосконалення системи регулювання відносин з суб'єктами бізнесу у
вказаній сфері. В статье освещены проблемы и перспективы развития самозанятости населения в
Украине, современные подходы к этой форме занятости. Уточнено понятие самозанятого населения,
определены основные причины возникновения самозанятости, выявлены резервы роста численности
самозанятого населения. Раскрыты особенности самозанятости в условиях информационного
общества и её преимущества. Обоснована необходимость государственной поддержки развития
самозанятости населения путём совершенствования системы регулирования отношений с субъектами
бизнеса в указанной сфере. The article, on the basis of the analysis of publications on issues of employment, including selfemployment,
as well as the observations of the author in this area, highlights the problems and prospects of selfemployment
in Ukraine.
The current theoretical approaches to self-employment are reviewed and summarized.
The notion of self-employment in the current economic environment is specified.
The main causes of self-employment and the transition of the Ukrainian population to work in a self-employment
are determined.
The correlation between the dynamics of the number of employees and self-employed on the basis of the analysis
of statistical data, and reserves of the growth of the self-employed population in Ukraine are revealed.
The features of self-employment in the information society are studied.
Modern forms of self-employment as a kind of business that have emerged in the transformation of the society
into the global information one are defined.The tendency to expand the self-employment scale in Ukraine's progress on the path of market reforms is
determined.
The advantages of self-employment as a form of employment are grounded.
The necessity of state support for self-employment by improving the system of regulation of relations with
business entities in this area is stated.